Duplex Ultrasound Assessment of Radial Artery Access Site: Complications and Clinical Outcomes. Issue 2 (June 2022) - Darwazeh, Ghaleb A.; Starr, Jean; Satiani, Bhagwan
Introduction: The radial artery is often utilized for invasive hemodynamic monitoring as well as an access site for arterial and cardiac catheterization. Complications requiring intervention, although uncommon, may have implications for future utilization of this site and harvesting for coronary bypass. We aimed to better define the occurrence and the risk factors associated with radial artery access (RAA). Methods: Patients referred for upper extremity arterial duplex (UEAD) examinations with clinical findings suspicious for complications after RAA between 2008 and 2016 were reviewed. Electronic medical records and vascular laboratory records were reviewed for demographics and peri-procedural data. Results: The radial artery was used for 19, 253 arterial lines, and 13, 402 cardiac catheterizations during the study period at our institution. During this time, a total of 131 patients were referred to our vascular laboratory for UEAD based on abnormal clinical findings after RAA. Sixty-two (47%) patients had undergone radial artery catheter (A-line) placement for hemodynamic monitoring, and 69 (53%) had left heart catheterization (LHC). Six patients required surgical intervention: 5 after A-line and 1 after LHC. A-line was more frequently associated with a positive UEAD finding compared with LHC (79% vs 57%, P = .007). Among patients with A-lines, there was no significant relationship between presence of a positive UEAD finding and the specialty or level of training of the operator, the number of attempts, the usage of ultrasound guidance, or catheter indwelling time. There was also no significant relationship between a positive UEAD finding and the size of sheath (5Fr vs 6Fr) among patients who underwent LHC. Conclusions: A positive UEAD finding in patients with clinically apparent complications after RAA is uncommon, and the need for surgical intervention is similarly infrequent. Follow-up UEAD studies may be useful to determine long-term patency of the radial artery and usability for future access or for coronary artery bypass grafting.